2006
DOI: 10.1111/j.1749-4486.2006.01289.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a voice prosthesis questionnaire to assess valved speech and its related issues in patients following total laryngectomy

Abstract: The voice prosthesis questionnaire is the first validated and reliable self-administered questionnaire designed specifically for evaluating valved speech and its related issues in patients who have undergone total laryngectomy. The voice prosthesis questionnaire has significant utility for audit, outcomes research and monitoring in this unique group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 11 publications
1
30
0
Order By: Relevance
“…A high Cronbach's alpha (>0.70) and Spearman's correlation (rho > 0.60) value indicate adequate internal consistency and test-retest reliability. 35 Validity. Construct and group validity were assessed by correlating speech item score with related constructs from the UWQOL questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…A high Cronbach's alpha (>0.70) and Spearman's correlation (rho > 0.60) value indicate adequate internal consistency and test-retest reliability. 35 Validity. Construct and group validity were assessed by correlating speech item score with related constructs from the UWQOL questionnaire.…”
Section: Methodsmentioning
confidence: 99%
“…Cronbach's a is the measure of the a coefficient, and a coefficient value of >0.70 suggests that the scale has adequate internal consistency. 22,28 Since Cronbach's a is a form of intraclass correlation, the values for heterogeneous subjects or responses tend to be high, whereas these values will be lower if the subjects or responses are similar to each other, as seen in the control group in the present study (Table 3). 29 Since the controls were normal volunteers with normal speech, they scored ''0'' for majority of the studied parameters for both connected speech and individual words, which resulted in the predominance of zero variance items.…”
mentioning
confidence: 80%
“…The Spearman's rank correlation coefficient values of >0.60 generally show a strong correlation: 0.40 to 0.60, moderate to substantial correlation; and <0.40, weak correlation. 22,28 Among patients the LSE scale in this study has shown significantly high internal consistency; strong intra-rater reliability for overall grade; intelligibility and articulation; and moderate to strong inter-rater reliability for grade, intelligibility, articulation, and nasality of speech for both connected speech and single words. Intra-rater reliability coefficients for nasality varied between mild and strong for both the connected speech and single words.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Again, we found that all sizes of the voice prosthesis were being used reflecting the variability and individuality of the length of the tracheo-oesophageal partition or party wall. The Blom-Singer valve was the most commonly used valve in our study, and possible reasons for this could be the fact that many variations exist, its low cost, easy availability and familiarity on the NHS and little or no difference on key issues such as speech and leakage compared with other leading brands [2,9] .…”
Section: Discussionmentioning
confidence: 99%